Knowledge of senior students concluding the courses of Dentistry and Medicine toward the interrelationship of periodontal diseases and systemic health (Research, Society and Development, 2020)
Background/Purpose This study evaluated the knowledge of last year's students of dentistry (DENT) and medicine (MED) regarding the association between periodontal disease (PD) and systemic disease (SD). Materials and methods: A questionnaire developed to evaluate the knowledge, attitudes and behaviors related to PD was applied for the students. Results: 287 students participated, 81 from DENT and 206 from MED. 47% of DENT students correctly answered all five questions of true or false, compared to 51% of MED students (p> 0.05). Between MED students, 67% never ask their patients if they have ever been diagnosed with PD; 51% never evaluate their patients for PD; 28% never refer their patients to a dentist; 95% didn’t receive PD training during the course; 61% believe that patients do not expect them to discuss/evaluate PD and 51% agree that discussing/evaluating periodontal condition is secondary to their role. For DENT, 12% never ask their patients if they have ever been diagnosed with PD, although 98% always do the evaluation, and 9% do not feel comfortable doing the periodontal examination. Conclusion: Although the students of both courses presented a good theoretical knowledge about PD and its association with systemic health, when approached regarding clinical practices, the results were unsatisfactory.